A Brief Screening Tool for Literacy Skills in Preschool Children: An Item Response Theory Analysis. (27th May 2020) - Ecalle, Jean; Thierry, Xavier; Magnan, Annie
In a large-scale study conducted in 4- to 5-year-old French-speaking preschoolers ( N = 12, 162), early literacy skills were assessed with four short tasks designed to investigate three domains related to learning to read: letter knowledge, phonological skills, and vocabulary. This tool was developed in response to the lack of available literacy screening tools for this population. Item response theory (IRT) analyses were used to examine the discrimination and difficulty parameters of each item. Then, a structural model confirmed that all the scores contributed to a latent ability, namely, early literacy. Three variables, namely, sociodemographic zone, age, and gender, are related to performance on literacy skills. Finally, an IRT with these variables as covariates confirms that all of them explained the difference in the scores in each domain except for zone in the case of letter-name knowledge (without significant link). This initial tool for French-speaking preschoolers could be used to identify children with early difficulties and help promote early language interventions to combat subsequent difficulties in learning to read.